Hälsokoll – Ett nytt sätt att få översikt över och dela sin hälsodata - Andersson, Ludvig; Christina, Meisoll (My University, 2023)
Purpose and scope: This report aims to explore the development of a proof-ofconcept android mobile application that provides the user with the possibility to log symptoms and medications, as well as provide the data to third parties. Method: The development followed an agile approach based on 16 user stories in groups and scrum sprints. Programming was performed in Android Studio with an emulated Google Pixel 4 with Android 12 and a physical Samsung Galaxy S8 with Android Pie. Depending on their difficulty, each user story was developed either individually with review of the other team member or in pair programming. Result: The final product was an application that allows for logging of fever, pain, and medication both now and retroactively. Users can set notifications both once or multiple times to be reminded to check fever or pain again or take the next medication. Data is kept secure from unauthorized access by storing all data locally on the user’s mobile. The user can even create more user profiles to log for other members of the family. Finally, the user also can filter their previous logging to what they want to see and export that to a PDF that can be transmitted to their caregiver. Most of these features are implemented as fragments to transfer data between different fragments. Conclusion: This project provides a working proof of concept that helps people to keep track of their health development and share the data with relevant parties.
Keywords: Android; smartphone; health; ehealth; mhealth; datasecurity